DESAIN PENGALAMAN BELAJAR PAI YANG IDEAL DI ERA DIGITAL - Suhernawati; Harahap, Nasrun (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study is motivated by the limited research on the design of learning experiences in Islamic Religious Education (PAI), despite its significant impact on student learning outcomes. The aim is to design an effective and relevant PAI learning experience model to address the challenges of 21st-century education. The method employed is a qualitative approach, incorporating a literature review from 2015 to 2025 and field observations. The results indicate that a holistic, innovative PAI learning experience design, which utilizes digital technology and participatory methods, enhances student engagement, understanding, and internalization of Islamic values, aligning with constructivist, humanistic, and behaviorist theories. In conclusion, the ideal PAI learning experience model integrates contextual approaches, digital technology, active methods, and holistic assessment. The study’s implications emphasize that such a design aligns with key learning theories, requires educators to consider student needs and characteristics, learning objectives, content, and methods, and calls for educators to improve their competencies. Furthermore, the government should provide training for educators and equip facilities to support effective learning. This research also opens opportunities for further studies to explore technology access gaps, develop innovative learning solutions and models tailored to students’ needs, and evaluate technology use to optimize learning outcomes.